Proton Magnetic Resonance Spectroscopy for Diagnosis of Non-Motor Symptoms in Parkinson's Disease - Guan, Ji-tian; Zheng, Xin; Lai, Lingfeng; Sun, Shuyi; Geng, Yiqun; Zhang, Xiaolei; Zhou, Teng; Wu, Huan-ze; Chen, Jia-qing; Yang, Zhong-xian; zheng, Xiao-hong; Wang, Jia-xu; et al. (Frontiers in Neurology, 2022)
Background:Parkinson's disease (PD) is normally diagnosed based on the clinical history and motor symptoms. However, more than 60% dopaminergic neurons in the substantia nigra have been lost when the motor symptoms occur. Predictive neurobiomarkers may help identify those potential PD patients having non-motor disorders. Up to date, few if any neuroimaging techniques have been described useful for non-movement disorders diagnosis in PD patients. Here, we investigated the alteration of metabolites in PD patients with non-motor symptoms including sleep, gastrointestinal and cognitive dysfunction in different stage of PD, by using the 1H-MRS. Methods:A total of 48 subjects were included between 2017 and 2019: 37 PD (15 males, age 47-82 years) and 11 health people (8 males, age 49-74 years). All participants underwent MRI and multi-voxel 1H-MRS examination within 3 days in admission. Six kinds of metabolites, including creatine (Cr), N-acetyl aspartate/creatine (NAA/Cr), N-acetyl aspartate/choline (NAA/Cho), choline/creatine (Cho/Cr), lipid/creatine (LL/Cr), and myo-Inositol/creatine ratio (mI/Cr) were tested among PD group and the control groups. Statistical analyses and correlation analysis were performed by using SPSS. p < .05 was considered statistically significant. Results:Compared late PD group with control group or early group, higher Cr ratio and lower NAA/Cr ratio were observed in the late PD group (P < 0.05). mI /Cr in the late PD group was also lower than that in the early PD group (P < 0.05). Regarding to the relationship between metabolites and non-motor symptoms, Cho/Cr was higher in sleep disorder group, whereas mI/Cr was lower in gastrointestinal dysfunction group in comparison with non-symptom groups. Moreover, Cr, Cho/Cr, mI /Cr, LL/Cr were identified to have higher concentrations in cognitive group in thalamus. Conclusions:1H-MRS is an advanced tool to quantify metabolic changes in Parkinson’s diseases. Three biomarkers (Cr, NAA/Cr, mI/Cr) were detected in late stage of PD, suggesting that these markers might be potential to imply the progression of PD. In addition, subgroups analysis showed that MRS of thalamus is a sensitivity region for the detection of cognitive decline in PD, and the alteration of neurochemicals (involving Cr, Cho, mI, and LL) may be promising biomarkers to predict cognitive decline in PD.